Environmental drivers of fungal community structure: a comparative high-throughput sequencing study of two geothermally distinct hot springs in Hefei, China - Zhang, Feng-Qin (Frontiers in Microbiology, 2025)
IntroductionThere are abundant hot spring resources in Hefei. This is the first study to analyze and compare the fungal diversity of Tangchi and Bantang hot springs in Hefei.MethodsThis study represents the comprehensive analysis of fungal diversity in two geothermally distinct hot springs (Tangchi and Bantang) in Hefei, China, using Illumina MiSeq PE300 sequencing of the ITS region.ResultsDespite their spatial proximity, Tangchi (63.9°C, pH 8.2) and Bantang (45.8°C, pH 6.5) showed stark contrasts in fungal community composition. A total of 934 OTUs were identified, with Tangchi exhibiting greater α-diversity and only 18.6% OTU overlap. Both systems were dominated by Ascomycota and Basidiomycota, yet genus-level divergences were substantial: Tangchi favored Rhizophydium, Aureobasidium, and Rhodotorula, while Bantang harbored Coniosporium, Trichomerium, and Aureobasidium.DiscussionComparative analysis with freshwater ecosystems revealed unique thermoadaptive strategies and reduced overlap with non-thermal fungal assemblages. These findings emphasize temperature and pH as critical drivers of fungal niche partitioning in geothermal systems and underscore the untapped biotechnological potential of thermophilic fungi.